Teaching About Religion at the State University: Taking the Issue Seriously and Strictly - Baird, Robert D. (Bulletin for the study of religion, 2020)
In 1983 Robert N. Minor and Robert D. Baird wrote a piece for The Bulletin that discussed what it means to teach religion academically in a public university in the United States. By dismantling other popular notions of what it meant to teach religion in a public university—such as the inculcation of values despite the preference this method shows for one religious system over another—the authors illustrate the flaws in these pedagogical styles and ultimately propose a new purpose for teaching religion. This new purpose they highlight strives not to promote one value system over another, or to propose one way of doing religion is right or wrong, but to promote understanding among students by showcasing the individuality that exists within religious traditions.